Public talk on Rabindranath Tagore: Asia’s first noble laureate - Quayum, Mohammad Abdul (2014)
An introductory talk on Rabindranath Tagore, highlighting some of the important aspects of his life and writings. Challenges and possibilities associated with translating his fiction was the main focus of the talk as it was tailored for the launch of my collected translation of Rabindranath's short stories, The Ruined Nest and Other Stories.